The Suitability of Tomini Bay Gorontalo for Marine Tourism: Opportunities and Challenges - Hamzah, Sri Nuryatin; Sahami, Femy M; Habibie, Sitty Ainsyah; Djunaidi, Sandrianto (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract    Highlight Research 1. The potential of coral reefs for marine tourism has been calculated. 2. The potential of coralfish for marine tourism has been identified. 3. Water quality parameters are supporting factors for the sustainability of marine tourism. 4. The suitability of snorkeling and diving tourism has been mapped.     Abstract The waters of Tomini Bay, which boast the longest coastline in Gorontalo Province at 572.5 km, hold significant marine tourism potential, warranting further study and development. This research evaluated the potential and suitability of marine tourism in the Tomini Bay Gorontalo area, specifically snorkeling and diving. Data were collected on coral reef conditions, reef fish communities, and water quality parameters from six locations, including Pinomontiga, Kurenai, and Kaisomaru Beach, as well as Dulanga, Bitila, and Lahe Islands. Coral reef conditions were assessed using the underwater photo transect method, while reef fish data were collected using the underwater visual census method. Physical water parameter data measured were temperature (°C), salinity (‰), pH, dissolved oxygen (mg/L), current speed (cm/s), and brightness (m). The analysis of coral cover was conducted using Coral Point Count with Excel extensions (CPCe), while the suitability for snorkeling and diving tourism was assessed using the Tourism Suitability Index. The results showed that most locations had moderate to excellent coral reef conditions, high coral and fish diversity, and water quality that supported marine tourism activities. Among the six locations studied, two, namely Pinomontiga Beach and Lahe Island, were rated highly suitable for snorkeling and diving, while Kaisomaru Beach was not suitable. Other places, including Kurenai Beach and Bitila Island, were rated as suitable. These results provide essential information for developing sustainable marine tourism in Tomini Bay Gorontalo and can serve as a reference for local government in planning environmentally friendly tourism activities.